2022
DOI: 10.15294/jipk.v16i1.29407
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Miskonsepsi Materi Kesetimbangan Kimia pada Siswa SMA Menggunakan Tes Three Tier Berbasis Web

Abstract: Miskonsepsi merupakan masalah besar yang telah menjadi pusat perhatian bagi para pendidik dan peneliti pendidikan pada mata pelajaran ilmu pengetahuan alam, khususnya kimia. Salah satu  materi dalam kimia yang dianggap siswa cukup sulit sehingga tinggi kemungkinannya untuk terjadi miskonsepsi adalah materi kesetimbangan kimia. Miskonsepsi pada siswa perlu diidentifikasi dengan cepat supaya dapat segera ditangani sehingga tidak menganggu pembelajaran selanjutnya. Penelitian ini bertujuan untuk mengidentifikasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Kesetimbangan kimia menjadi salah satu bahasan dalam ilmu kimia yang sulit dipahami dikarenakan berisi konsep yang sebagian besar bersifat abstrak, sehingga untuk memahaminya dibutuhkan pengamatan secara langsung tentang fenomena yang terjadi (Amaliyah dan Nasrudin, 2019). Di dalam materi kesetimbangan kimia terdapat sub materi yang dianggap sulit oleh peseta didik untuk dipahami yaitu pergeseran kesetimbangan, dikarenakan peserta didik mengaplikasikan prinsip Le Chatelier tanpa memahaminya (Permatasari et al, 2022). Prinsip Le Chatelier merupakan landasan dalam menjawab pernyataan yang berkaitan dengan pergeseran kesetimbangan.…”
Section: Pendahuluanunclassified
“…Kesetimbangan kimia menjadi salah satu bahasan dalam ilmu kimia yang sulit dipahami dikarenakan berisi konsep yang sebagian besar bersifat abstrak, sehingga untuk memahaminya dibutuhkan pengamatan secara langsung tentang fenomena yang terjadi (Amaliyah dan Nasrudin, 2019). Di dalam materi kesetimbangan kimia terdapat sub materi yang dianggap sulit oleh peseta didik untuk dipahami yaitu pergeseran kesetimbangan, dikarenakan peserta didik mengaplikasikan prinsip Le Chatelier tanpa memahaminya (Permatasari et al, 2022). Prinsip Le Chatelier merupakan landasan dalam menjawab pernyataan yang berkaitan dengan pergeseran kesetimbangan.…”
Section: Pendahuluanunclassified
“…According to Chang & Overby (2011) stated that students have difficulty in chemistry compared to other sciences. Difficulties in understanding chemistry are caused by the characteristics of abstract concepts (Permatasari et al, 2022). According to Sunyono in Sari et al, (2018) states that the characteristics of the concept of chemistry are in the form of multiple representations, namely the practice of representing the same concept through various forms, which include verbal mode, visual mode, symbolic, graphic, and numerical to describe the concept on macroscopic, submicroscopic, and symbolic levels of representation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kirbulut & Geban (2014) misconceptions are defined as students' understanding of accepted concepts that are different from scientifically accepted concepts. Misconceptions must be handled quickly and precisely because misconceptions tend to persist and can hinder learning, make learning less meaningful, cause ongoing misconceptions, and can hinder the development of science and technology (Bayuni et al, 2018;Luqman & Abbas, 2019;Permatasari et al, 2022;Putra et al, 2020). In this study, the researcher wanted to see the analytical profile of the five-tier diagnostic test used in high school chemistry lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research conducted by Rumapea & Silaban (2022) Regarding the development of a Three-Tier Multiple Choice diagnostic test instrument based on an Android Based Test, the results obtained that the instrument can be used to analyze the level of understanding of students' concepts on the subject of reaction rates. The last research conducted by Permatasari et al (2022) discusses the identification of students' understanding levels using the Web-Based Three Tier Test. This study showed that students' misconceptions could be identified with the average percentage of students' misconception levels, namely 43.91-62.06%.…”
Section: Introductionmentioning
confidence: 99%